About plagiarism, authorship and other ethical issues of publications - López-López, Wilson (2015)
In recent times, there has been an increase in the frequency with which reports, complaints, and other discussions about the authorship of articles or the unrecognized use of document contents by other authors (practice known as plagiarism), are being recoded. Although this is not a new topic nor restricted to the non-recognition of an idea, the problems associated with the improper use (ethical) of information are being increasingly discussed. For instance, topics of discussion are: problems in the collection, use, careless analysis or discussion of data with misconduct or falsification (fraud), and undeserved authorship or duplication of work, or parts thereof, by the same authors in scientific publications. As discussed by Gallegos, Berra, Benito, & López-López (2014) and López-López (2013, 2014), it is probable that the dynamics and pressure of knowledge production are promoting the frequent occurrence of these behaviors. Nonetheless, although these problems are now more evident, they are at the same time more controllable. Firstly, the technological revolution in information and communications allows the information and knowledge to flow quicker, more efficiently, faster, and with an almost global coverage, now a days, as compared to any other time in history. Thus, it is easier for a community to evidence the use of contents as well as the ways of collecting and analyzing data, and generating forms of control. Moreover, publishers currently demand more often the primary databases, data files, and even the drafts and analysis plan of the results, before their collection1. In addition, journals count, now a day, with teams that are responsible not only for verifying some of the information provided, but also for verifying the analysis derived therefrom. Furthermore, some journals have started to demand clarification of the roles in the production of articles (generation of ideas, participation in data collection, analysis of data, writing of the manuscript, the discussion of document, the revision of the text, the translation performed, among many others). This is done under statements of agreement between the authors of the document (Allen, Brand, Scott, Altman, & Hlava, 2014). Secondly, throughout the editorial process, the scientific content undergoes peer review. In general, we expect that reviewers assess not only the relevance, scope, theoretical and methodological strength, but also the originality of the content. Moreover, reviewers may detect problems in data and in their analyses. Although this is not an exhaustive and infallible process, anecdotally, we have been able to detect some documents published with similar data, thanks to the review process. Nevertheless, the growth in the number of articles to assess can jeopardize the review system and consequently the possibility of detecting this type of conducts (Arns, 2014). Thirdly, in the case of plagiarism, publishers count with softwares that enable them to identify a document, or sections of a text, that are in the network. In any case, sooner or later, it will be evident for the whole community that an author / researcher has committed an alteration or a fault. For this reason, the risk of using content without due recognition is higher, and those who take the risk will evidently have to assume the consequences that the community and the law have stipulated to this type of behavior. Despite these items mentioned above, as editors we must be more explicit about the ethical requirements of information. This leads us to join worldwide efforts and assume, for instance, the guidelines of the Committee on Publication Ethics (COPE) (http://publicationethics.org/) (Yong, Ledford, & Van Noorden, 2013). Thus, from this number, Universitas Psychologica will place a greater emphasis on the use of the COPE guidelines, and will seek to promote them as a guide of conduct for the publications in the region, in the various networks in which we participate. Similarly, a few months ago an emphasis started to be made on the report of the ethical aspect of articles, since this is a criterion that, in some cases, can become grounds for immediate rejection of the articles. This measure goes beyond the traditional “informed consent” and requires an ethical review of the research that has been performed, regardless of the field of psychology or the type of research. Researchers should be aware of the ethical role in the collection, management, implications and publication of information. The best way to ensure this process is by subjecting it to an institutional or state committee, which supports the reported actions (Dolgin, 2014). Psychology, in our region, is having a rapid expansion. The dynamics of production are affecting our communities and may be generating undesirable practices in the field of publications. Therefore, it is necessary that we generate discussion of the ethical issues of publications, and that we seek for more control systems, capable of preventing publication under unethical conditions. Additionally, we should evaluate the impact and costs on local publications and overall on the region in development (economic, political, social and scientific), caused by the retraction and the malpractices associated with the rush to publish and the consequent overflow. By joining international control and practices, we will globalize our processes and will increase the interest and confidence of non-Hispanic communities in the production of Latin America. Wilson López López Editor